Comparison of different rhythmic auditory stimuli on prefrontal cortex cortical activation during upper limb movement in patients with Parkinson’s disease: a functional near-infrared spectroscopy study - Wang, Jie; Li, Yingqi; Wang, Yingpeng; Wang, Congxiao; Qie, Shuyan; Jin, Zhaohui; Du, Wenjun (Frontiers in Neurology, 2024)
Background: A large number of literatures show that Rhythmic auditory stimulation (RAS) can effectively improve Parkinson's disease(PD) patients' gait speed, frequency and speed. Its application and curative effect on upper limb motor function is relatively few. Objective:By studying the immediate effect of RAS with different rhythms on the prefrontal cortex (PFC)blood oxygen response during upper limb movement in PD patients, this study discusses the potential neurophysiological mechanism of RAS on upper limb movement in PD patients, which is expected to provide guidance for patients with upper limb dysfunction such as Parkinson's disease. Methods:In this study,31 PD patients with upper limb static tremorswere recruited to complete the nail board task on the healthy upper limb under the baseline rhythm, slow rhythm and fast rhythm provided by the therapist. At the same time, fNIRS was used to observe the blood oxygen response of PFC.Results:There was no significant main effect onsidein all brain regions (P > 0.05), and there was no interaction between rhythm and side (P > 0.05); Except lPFC, the main effect of rhythm in other brain regions was significant (P < 0.05), and ΔHbO increased with the change of rhythm. Paired analysis showed that there were significant differences in ΔHbO between slow rhythm and baseline rhythm, between fast rhythm and baseline rhythm, and between slow rhythm and fast rhythm (P < 0.05);TheΔHbO of rPFC, lDLPFC and rDLPFC were significantly different between slow rhythm and fast rhythm (P < 0.05); There were significant differences in the ΔHbO of BA8 between slow rhythm and baseline rhythm, and between slow rhythm and fast rhythm (P < 0.05).Conlusions:RAS may be a useful upper limb rehabilitation strategy for PD patients with upper limb dysfunction. At the same time, RAS with different rhythms also have different responses to PFC blood oxygen during upper limb movement in PD patients, so that we can design interventions for this kind of cortical mechanism.Identifying the neurophysiological mechanism of RAS on upper limb movement in PD patients may help clinicians customize rehabilitation methods for patients according to clues, so as to highly personalize upper limb training and optimize its effect.